Just write : here's how - Dean Myers, Walter (U.S.A. : Scholastic INC, 2012)
I'm often asked why I write for young people. My own experiences as a teenager were so intense that I keep coming back to that period of my life to explore and to make sense of it in a way that defines who I am today.
CONTENTS PROLOGUE : Why I'm a writer CHAPTER I: Roll up yout sleeves CHAPTER 2: Something old, something new, something borrowed, something blue CHAPTER 3: Hello, voices inmy head CHAPTER 4: Map it out CHAPTER 5: Lights, camera, action CHAPTER 6: Nice to meet you CHAPTER 7: What's going on? CHAPTER 8: Where´s the fires? CHAPTER 9: What's it to you? CHAPTER 10: Get it together CHAPTER 11: So what are you going to do about it? Y otros 11 capítulos más...
Incluye Contents
Keywords: ENGLISH LITERATURE; SHORT STORIES